The Influence of Employee Incentives and Work Motivation on Employee Performance - Lina Kartika (Journal of Economic, Management and Entrepreneurship, 2024)
This study aims to analyze the influence of employee incentives and work motivation on employee performance, focusing on courier employees at JNT Kota Batu, East Java. The research employs a quantitative method with an explanatory approach to identify the direct and indirect effects of incentives on motivation and employee performance. The population consists of 235 couriers, and the sample size was determined using the Slovin formula with a 5% margin of error, resulting in 148 respondents. Data were collected through structured questionnaires and analyzed using path analysis. The results reveal that employee incentives significantly influence work motivation and employee performance, both directly and indirectly through motivation. Motivation plays a key mediating role in strengthening the relationship between incentives and performance. These findings suggest that enhancing work motivation through effective incentive programs can substantially improve courier performance. This research contributes theoretically by emphasizing the mediating role of motivation in the relationship between incentives and performance and offers practical insights for JNT managers to design strategies that optimize employee performance.